Verspreide geschriften. [Voorw. van C. Snouck Hurgronje, F.M. van Asbeck, W.J.M. van Eysinga, e.a.] (Haarlem enz.)
1. Omtrek en methode der rechtswetenschap. Leiden. "Historische schetsen". Grotius. Thorbecke